Rāingān kāntittām pramœ̄nphon kānphatthanā sētthakit læ sangkhom khō̜ng prathēt : nai raya phǣn phatthanā chabap thī 10 (Phō̜. Sō̜. 2550-2554) (Samnakngān Khana Kammakān Phatthanākān Sētthakit læ Sangkhom hǣng Chāt, 2011)
Evaluation report of the socio-economic policy and development plan of Thailand for 2007-2011.